(untitled) (Experimental biology, 2015)
The paper presents the frequency and types of chromosomal aberrations in bone marrow cells in 19 children with leukemia. As a result of cytogenetic research to quantitative and structural features of chromosomal mutations, depending on the types of the disease. Numerical and structural chromosome aberrations were detected in 4 patients, the frequency of occurrence was 21.05%. Chromosomal aberrations were observed in 18 patients – 94.74%. By type of chromosomal aberration frequency was: translocation – 63.16%, deletions – 31.58%, marker chromosomes – 10.53%. The frequency of mosaic karyotypes options was 21.05%. In 2 patients with children of the same type installed chromosomal abnormalities involving 11 chromosome – del(11)(p14), the third patient also revealed a translocation involving chromosomes 11-th – t(11; 14)(p13; q11). In 3 patients a monotype translocation – t(8; 21)(q22; q22). Most rarely found in Western Europe and Russia mutation del(6)(q21) was observed in the patients examined at a frequency of 15.79%